Effects of ionic structures on shear thickening fluids composed of ionic liquids and silica nanoparticles. Issue 85 (31st August 2016) - Qin, Jianbin; Zhang, Guangcheng; Ma, Zhonglei; Li, Jiantong; Zhou, Lisheng; Shi, Xuetao
Abstract : Shear thickening fluids (STFs) are energy dissipative materials and affected significantly by the properties of the dispersing media. Abstract : Shear thickening fluids (STFs) are energy dissipative materials and affected significantly by the properties of the dispersing media. Most of the dispersing media are polymeric or oligomeric fluids, and few studies have made ionic liquids (ILs) as the dispersing media. Since the properties of ILs are strongly dependent on its' ionic structures, the shear thickening behavior of STFs composed of ILs must be influenced by the ionic structures. The rheology and viscoelasticity of STFs of hydrophilic silica nanoparticles in ILs with different ionic structures were investigated systematically. The experimental results demonstrated that the dispersions in hydrophilic ILs displayed shear thickening behavior, while dispersions prepared by hydrophobic ones appeared as a colloidal gel and displayed shear thinning. With changing the length of the alkyl chain substituent on the organic cation, the shear thickening behavior was transformed. Shear thickening behavior was enhanced for the introduction of hydroxyl on the organic cation. Ionic structures influence the interactions between silica nanoparticles and ILs through the hydrogen bonds, and the shear thickening behavior may be induced by the formation of nanoparticle aggregation. The dynamic stabbing resistance, quasi-static tensile strength and conductivity of Kevlar fabric composites treated by STFs composed of ILs were enhanced observably, and the electromagnetic shielding property was improved to a certain degree.